PENGARUH INTENSITAS CAHAYA DAN PUPUK CAIR LCN TERHADAP PRODUKSI BAWANG MERAH (Eksperimen untuk Bahan Problem Based Learning) - Forniawan, Ary; Sujarwanta, Agus; Muhfahroyin, Muhfahroyin (Lembaga Penelitian UM Metro, 2017)
North Lampung Regency is one of the immature onion production. The environmental factors which affecting are the intensity of sunlight as well as liquid fertilizer. The objectives of the research were to prove empirically effect of sunlight intensity and LCN liquid fertilizer on onion production. The research design was using RAL (Completely Randomized Design). The samples of each treatment were 64 plants and 16 replications with randomly sampling. The data obtained were analyzed by 2-way ANOVA and Tukey's advanced test. From the data analysis concluded (1) there is effect of sunlight intensity on onion production, (2) there is effect of LCN waste liquid fertilizer on onion production; (3) there is interaction effect between sunlight intensity and LCN liquid fertilizer dosage on onion production (4) there is effect of onion production on LCN 300 ml liquid fertilizer dose factor which given 70% sunlight intensity is higher than 35% sunlight intensity (5) there is not real effect of onion production on the factor of pineapple liquid waste (LCN) 200 ml which given 70% sunlight intensity is lower than 35% sunlight intensity.